Metal Complexes of Macrocyclic Schiff-Base Ligand: Preparation, Characterisation, and Biological Activity - Riyadh M. Ahmed; Enaam I. Yousif; Hasan A. Hasan; Mohamad J. Al-Jeboori (The Scientific World Journal)
A new macrocyclic multidentate Schiff-base ligand Na4L consisting of two submacrocyclic units (10,21-bis-iminomethyl-3,6,14,17-tricyclo[17.3.1.18,12]tetracosa-1(23),2,6,8,10,12(24),13,17,19,21,-decaene-23,24-disodium) and its tetranuclear metal complexes with Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) are reported. Na4L was prepared via a template approach, which is based on the condensation reaction of sodium 2,4,6-triformyl phenolate with ethylenediamine in mole ratios of 2 : 3. The tetranuclear macrocyclic-based complexes were prepared from the reaction of the corresponding metal chloride with the ligand. The mode of bonding and overall geometry of the compounds were determined through physicochemical and spectroscopic methods. These studies revealed tetrahedral geometries about Mn, Co, and Zn atoms. However, square planar geometries have been suggested for NiII and CuII complexes. Biological activity of the ligand and its metal complexes against Gram positive bacterial strain Staphylococcus aureus and Gram negative bacteria Escherichia coli revealed that the metal complexes become more potentially resistive to the microbial activities as compared to the free ligand. However, these metal complexes do not exhibit any effects on the activity of Pseudomonas aeruginosa bacteria. There is therefore no inhibition zone.